Emerging patient-specific treatment modalities in head and neck cancer – a systematic review. (3rd April 2019) - Elicin, Olgun; Cihoric, Nikola; Vlaskou Badra, Eugenia; Ozsahin, Mahmut
ABSTRACT: Introduction : Head and neck cancer (HNC) is an immunosuppressive disease that demonstrates heterogeneous molecular characteristics and features of tumor–host interaction. Beside radiotherapy and surgery, the current standard of care in systemic treatment involves the use of cytotoxic chemotherapy, monoclonal antibodies (mAbs), and tyrosine kinase inhibitors (TKIs). There are also other modalities being developed under the category of immunotherapy, but they are overshadowed by the recent advancements of immune checkpoint inhibitors. Areas covered : This systematic review covers recent advancements in 'patient-specific' treatment modalities, which can be only administered to a given patient. Expert opinion : Currently, patient-specific treatment modalities in HNC mainly consist of active immunotherapy using adoptive cell therapies and/or gene engineered vectors. Despite the slow pace of development, the interest continues in these treatment modalities. The future of HNC treatment is expected to be guided by biomarkers and personalized approaches with tailored combinations of local treatments (radiotherapy, surgery), systemic agents and immune system modulation. Systematic research is required to generate robust data and obtain a high-level of evidence for the effectiveness of such treatment modalities.